Incidence of the information system in the administrative management of the University for Andean Development - Taipe Oncebay, Lidia (2021)
The objective of the research to determine how the modeling of an information system affects the administrative management of the university. Information systems are included in all quality evaluation models, it is important in the evaluation and accreditation processes of university education, the modeling of the system shows the situation of regular operations so that administrative personnel can plan, organize, direct and control. In order to improve the quality of work, have necessary and timely information for decision making. Hence, we ask ourselves, in what way does the modeling of an Information System affect the Administrative Management of the University for Andean Development? Applied research, descriptive correlational design and to verify the hypotheses, the Pearson correlation coefficient of the Analysis showed that there is a very strong positive correlation between the variables. It was concluded that the modeling of an information system has a positive and significant impact on the Administrative Management of the University.